Examining a Tuanku's Political Power in West Sumatra - Welhendri Azwar; Yuli Permatasari; Mufti Ulil Amri (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
This study examines the authority of a tuanku, a leader of the tarekat (mystical teaching) community in West Sumatra, Indonesia—a charismatic figure with a significant role in the region's socio‐ political landscape. He issues political statements or ‘political fatwa’ regarding a certain issue to help determine choices. As such, political leaders seek to win his favor for an advantage in political contests. Data were collected from in-depth interviews with teachers and congregational members of the tarekat community to examine a tuanku's charismatic authority in the socio-political dynamics. The study reveals that a tuanku’s influence is strong, his understanding of politics is closely related to the religious understanding of the tarekat school, and his charisma impacts the political choices of the tarekat community. This study contributes to the literature by providing evidence of a religious figure's charismatic authority in West Sumatra's socio‐political dynamics.